The beginning of coinage in the Cimmerian Bosporus (a hoard from Phanagoria) - Kuznecov, Vladimir Dmitrievič 1953-; Abramzon, Michail Grigorʹevič 1961- (Peeters, 2021)
This book is devoted to the only hoard of the earliest silver coins minted in the Cimmerian Bosporus (Kerch Strait). It was hidden in a dwelling destroyed by fire in 480 BC during an enemy attack on Phanagoria. The widespread opinion in academic literature is that Panticapaeum was the first Bosporan city to mint coins - in the middle of the 6th century BC or a little later. But the discovery of a hoard whose deposition date is very well established enables us to date the beginnings of coinage on the shores of the Kerch Strait to the 490s BC. The authors propose that the coins were minted not in Panticapaeum but by a union of Greek cities under the umbrella of the temple of Aphrodite Ourania Apatouros, an extra muros temple, 'most famous' in the words of Strabo, already established in the 6th century BC in Phanagoria. With the coming to power of the Archaeanactids in Panticapaeum, about which Diodorus Siculus provides information, that became the dominant city of the Cimmerian Bosporus. It started to mint coins with the (Greek) inscription 'pan'.
Keywords: Epigraphik; Münze; Münzfund; Archäologische Stätte; Phanagoreia